Aspek Fonologis sebagai Strategi Humor dalam Dakwah Ustadz Abdul Somad (UAS) - Arina Khairanis; Sawirman Sawirman; Rina Marnita (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
This article aims to describe the phonological aspectsused to build humor in Ustadz Abdul Somad's (UAS)preaching. The data in this study are humorousspeech which contains elements of sound andmeaning play. The technique of playing sound isdetermined by referring to the formula for thephonological aspect of humor formulated by Wijana.The data were obtained using the observation methodwhich was supported by the note taking technique.The data was collected using the UninvolvedConversation Observation Technique method. Thedata in this research were analyzed using thereferential equivalent method with the comparativereferential technique proposed by Mahsun, namely bycomparing the play of sound and the meaning with thereferent. From the results of data analysis, it wasfound that there were seven sound playing techniquesused by UAS to create humorous utterances in hispreaching, namely: sound substitution, soundpermutation, sound insertion, sound addition, soundimpingement, sound preservation, and pause removal.